PEMODELAN DATA PANEL SPASIAL PERTUMBUHAN EKONOMI DI INDONESIA - Muhammad Azis Suprayogi (LPPM-ITEBA, 2023)
Gross Regional Domestic Product (GRDP) is an indicator that can be used as a tool to measure economic growth in a certain period using either current prices or constant prices. There are several variables that are thought to have an effect on GRDP, namely foreign investment, government spending, the labor force participation rate, and the human development index. This study conducts modeling to obtain factors that influence GRDP in Indonesia. This study involves spatial effects using the SAR and SEM models. The results show that the SAR fixed effect model is the best model.